(untitled) (Journal of Nepal Geological Society, 2014)
An approach towards integrated modelling of 3D geology and landslide susceptibility was performed with the application of GOCAD and GIS. Rock unit outcrops and orientation vectors were utilised in 3D geological modelling (geomodelling) whereas landslides and their causative variables were evaluated in the susceptibility model. Occurrence of landslides in the modelling site is the direct result of major rainstorms (extreme weather events) and their spatial localisation is greatly controlled by slope gradients, structural aspect of geological settings, and human interventions. The probability of future landslides was predicted through statistical algorithms (multivariate technique of logistic regression) and modelling result was validated by computing success rate in which AUC value is 93.78% indicating the model is valid with prediction accuracy of 0.5 to 1 (total area) and confirming the selected variables have positive influence on landslide susceptibility. Finally, 3D geological and landslide susceptibility models were integrated to illustrate virtual reality of the scenario.